Cadangan penambahbaikan susun atur ruang perniagaan tingkat bawah di Kompleks Membeli-belah Warta, Bangi - Hairulliza Mohamad Judi,; Nur Rabiatul Adawiyah Kae Ahmad Daniar,; Nor Atiqah Abdul Majid,; Nurul Syuhada,; Nurazmah Mat Nor, (Penerbit ukm, 2010)

(untitled)
Good facility layout involves preparation of material requirement, arrangement of physical equipment, and use of space in the best way to achieve maximum efficiency and smoothness. This study examines the layout practice of the ground floor area in Warta Shopping Complex in Bandar Baru Bangi and proposes a new layout to overcome the existing problems. Therefore, a number of visits and observations have been made on this facility, and issues and problems related to the layout was collected based on questionnaires distributed to 30 users. Then, a new layout suggestion is proposed and a visualisation environment is developed using the Google SketchUp software. A significant layout problem is related to crowded space that hinder visitors’ movement to shop around. Furthermore, basic facilities for customers such as chairs, information, and sign boards are not in a satisfying level. Facilities for disabled people, such as proper paths for those on wheel chairs and toilets, are not given enough attention by the management. Improvement to overcome these problems is proposed in a virtual environment. In this virtual environment, users could visualise the use of space, evaluate sales units relationship, ensure smoothness of visitors movement, and consider safety issues